Efeitos da sobrecarga crônica de ferro sobre o ventrículo direito e vasculatura pulmonar de ratos - Rodrigues, Sabrina Bertoli (2017)
Although it is essential for homeostasis in uni- and multicellular organisms, including mammals, excessive iron (Fe) levels can be harmful. In fact, patients and animal of iron overload exhibit damage and dysfunction in different systems, such as cardiovascular. Due to this potential effect of iron overload leading to vasculopathy, and evidences associating some clinical conditions of hemosiderosis and pulmonary hypertension, this study aimed to identify possible changes in vascular reactivity of pulmonary resistance arteries of rats exposed to different iron loading and investigate the underlying mechanisms. For this, the rats were distributed in groups and injected i.p. with iron-dextran at 10, 100 or 200 mg/Kg/day (severe overload), five days a week for four weeks, and compared with a group receiving saline injections (as control). There were reduced weight gain with Fe treatment at the highest doses, with Fe serum levels and tissue deposits indicating significant overload, confirming our experimental model. In addition, particularly in the group treated with the highest dose (200 mg/Kg/day), there was right ventricular (RV) hypertrophy and normal left ventricle (LV) morphology and function, suggesting that RV remodeling is not related to a possible LV failure. Associated with RV hypertrophy, we demonstrated concentric hypertrophy with reduction of internal diameter of pulmonary resistance arteries, as well as increased vasoconstrictor reactivity to TP receptor agonist (U46619) in the in vitro studies. There was reduced nitric oxide bioavailability and increased production of reactive oxygen species, which seems to be mediated by an increase in the gp91phox subunit of NADPH oxidase. In addition, the increase in superoxide anion (O2 •- ) appears to be dependent on the activation of the type 1 receptor for angiotensin II (AT1), since the incubation with the AT1 antagonist losartan prevented both vascular hyperreactivity and increased O2 •- detection in the Fe group. Therefore, we can assume that vascular dysfunction and pulmonary hypertension may establish an important phenotype to be investigated in iron overload, besides being a possible therapeutic target to mitigate the damages caused in this condition, such as RV failure for example, in addition to other complications.